Pedagogical chicken: a space for scientific literacy in the science club - Sabrina Silveira da Rosa; Andressa Luana Moreira Rodrigues; José Vicente Lima Robaina (Universidade Federal do Norte do Tocantins, 2021)
This article aimed to verify if the activities developed in the Science Club based on the reality of the students contributed to a significant learning of the students of the 3rd, 4th and 5th years of a school in the countryside. In order to carry out this research, eight activities were carried out in two months, which involved the construction of a chicken coop, the evolution of the land and a study on the hens. To collect the data, a book with the studied contents was built. In the analysis of the data it was used the Discursive Textual Analysis where it was concluded that the Science Education in the school of/in the countryside, starting from the reality of the students through the Science Club, potentiated a significant learning.